A SEGURANÇA ALIMENTAR E NUTRICIONAL DO PÚBLICO INFANTO-JUVENIL: O LEITE COMO COMPONENTE - Thais Regina Mezzomo; Juliana Nadal (Demetra, 2014)
Breast milk is the first food of the newborn, the only one capableof doubling the weight of the infant in its first months of life andcarrying out strong brain development. However, other kindsof milk, such as bovine milk, are usually included in infantnutrition. Thus, as it has been known that the right to grow upwith the best possible health is a fundamental right of every child,and provided by the Convention on the Rights of the Child. it isnecessary to know the importance of bovine milk for the foodsecurity of children and adolescents. Therefore, a literaturesurvey was conducted in SciELO and MEDLINE databases forpublications in the last decade. In this review it was observedthat dairy products provide about 50% of daily calcium needsworldwide and mainly contribute to the development of healthybones and healthy growth of children over 2 years old. However,the literature shows the relationship between bovine milkconsumption and the occurrence of anemia, food allergies andtype 1 diabetes. Thereby, it is observed that feeding practices aredeterminants of health in childhood and they are subject to thepurchasing power of households. So public policies in all regionsof the country should be deployed to ensure that all Brazilianchildren and adolescents are supplied with necessary quantity andquality not only of milk, but all other kinds of food, accordingto their age, thus ensuring Food and Nutritional Security of thechild- juvenile population.